Price elasticities of meat, fish and plant-based meat substitutes: Evidence from store-level Dutch supermarket scanner data - Zhaoxin Liu; Erik Ansink (Tinbergen Institute, 2024)
Reducing meat consumption has become a global policy target due to rising environmental, health, and animal welfare concerns. We provide novel evidence on how price change in real life affects grocery shopping behavior in the Netherlands. We focus on price-induced behavioral response among major meat categories (beef, pork, and poultry), fish, and the emerging product category of plant-based meat substitutes (PBMS). Our analysis is based on detailed weekly transaction data from approximately 1,500 products in 884 stores from several retail chains between 2015 and 2018. The own- and cross-price elasticities are estimated via a Quadratic Almost Ideal Demand System model, where we instrument the endogenous prices by the average prices from nearby stores. Our results show that all animal products have inelastic own-price elasticities, except for pork (-2.1). PBMS have a significant positive own-price elasticity (1.52), which we explain by the increasing variety of high-quality PBMS products. We also show that PBMS are price complements for beef, poultry, and fish. This study contributes to the policy discussions on a carbon meat tax and the protein transition by providing key statistics on price elasticities.
Keywords: Q1; D1; D4; 330; Consumer demand; meat; fish; plant-based meat substitutes; price elasticity